Body measures, growth curves and body weight prevision of alpacas (Vicugna pacos) reared in Italy - Michela Ablondi; Alberto Sabbioni; Giulia Esposito; Valentino Beretti; Vittoria Asti (Italian Journal of Animal Science, 2023)
Alpacas represent an exotic species for Italy, introduced no more than 20–30 years ago. Nevertheless, they are currently the most widespread camelid species reared in this country, highlighting the growing interest in breeding this species. So, it is useful to assess parameters on their growth in relation to the new environment. Thus, body weight and body measures were recorded on 49 healthy alpacas of Huacaya type (27 females, 22 males), along a period of 27 months. Overall, 111 individual observations were made. Data were analysed by ANOVA, as growth curves were estimated by applying the Gompertz’s model. Multiple regression was finally used to estimate body weight from body measures. Body weight and linear measures, except for the distance between iliac crest and the length of the rump, were influenced by the category (calves, yearlings, adults) and by the age class within category (p < 0.05), while gender and interaction between gender and category were never significant (p > 0.05). Asymptotic weigh of males was 8.25% higher than females (p < 0.05). Moreover, males at maturity had higher withers (+0.96%), longer body (+2.70%) and chest measurements (+3.18%) than females. Asymptotic rump width (both at the ilium and at the ischium) was higher in females (respectively + 6.19%; +12.90%). According to our work, the best equation for the estimate of body weight from body measures was the following: 5.691 + 0.00005624 * chest circumference3 + 0.00002298 * trunk length3 − 1.155 * rump width between ischial tuberosities + 0.00001545 * height at rump3 (R2=0.957; SE of estimate = 4.36 kg), that is important for a better management of the species.